Pengaruh Mata Kuliah Agama Islam Terhadap Pemahaman Tauhid dan Syirik Mahasiswa Taruna di Program Diploma Pelayaran Universitas Hang Tuah - Prawirosastro, Carlos Lazaro; Hidayat, Sapit (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2018)
The first goal of National Education is to make learners have faithful and devoted to God Almighty. Islamic Education in PTU also have a role in making the student as a pious man, while most major faith and the first is believe one God, Allah and do not shirk to Him. Today there are many human actions and beliefs that are not suitable with the national education goals. Based on the background of the problems mentioned above, it can be formulated the statement of the problem; first how is Islamic Education subject in PDP UHT and learning outcomes?; second how is the understanding of Tawheed and Shirk Student PDP UHT?; Third How is the influence of Islamic Education subject on Understanding Tawheed and Shirk Student PDP UHT Surabaya?. This research is quantitative research, the goal is to find a correlation between two variabels, Islamic Education Subject as x variabels and understanding on Islam Tawheed and Shirk of Student PDP UHT as y variabels. Methods of data collection: observation, interviews, documentation and questionnaires. While the method of statistical analysis using Product Moment. Based on the analysis of the data obtained, it can be concluded as follows: First Islamic Education subjects of PDP UHT is very good. The students achieve an averag of 80, which if consulted with assessment standards SBAK PDP UHT including high kriteria predicated very good; Second the Understanding of Tawheed and Shirk Student PDP UHT is not good, it is proved by the data analysis with an average yield percentage is 48% which if consulted with the standards provided by Suharsimi Arikunto lies in the range (40% - 55% ) is less well categorized; Third It is found that Islamic Education Subject influence on the understanding of Tawheed and Shirk Student PDP UHT, but considered very weak or very low. This is evident from the results of the acquisition of statistical calculation that shows the results of 0.117 that if consulted with interpretation table r classified category of very weak or very low. The rxy results when consulted in the significance level of 5% and 1% yields are lower so that the consequence is the null hypothesis (Ho) or nil stating that there is no significant positive effect between islamic education subject on Understanding Islam Tawheed and Shirk UHT PDP Students accepted or approved, and the alternative hypothesis (Ha) or work which states that there is a positive influence rejected.